In Vitro Inhibition Test of Turmeric and in Vivo Total Bacterial Count in the Intestinal Digesta of Mojosari Duck Fed Diet Containing Graded Levels of Turmeric - Ardiansyah, Widiastuti; Achmad, Dewi Shinta; Akbar, Muh Firyal (Newinera Publisher, 2024)
This study aimed to determine the inhibition value of turmeric (Curcuma longa) against Salmonella and Escherichia coli and evaluate the bacterial population in the small intestinal digesta of Mojosari ducks. This study was arranged using a Completely Randomized Design (CRD) with six treatments and four replications; eachreplication consisted of eight Mojosari ducks.The in vitro study used four treatments of different concentrations of turmeric, consisting of Control/only water (C0), turmeric 98% + 2% water(C1), Probiotic 98% and 2% water (C2), turmeric 92%, and probiotic 8% (C3),and Bacitracin 92% + water 8% (C4). Then, the inhibition zone diameter was measured using the agar well diffusion method. On the other hand, the in vivo study was carried out by employing 192 Mojosari duck raised for 60 days. They were given the following dietary treatments, namely T0= basal diet, T1= basal diet supplemented with turmeric 0.2%, T2= basal diet supplemented with supplemented with turmeric 0.8%, T3= basal diet supplemented with turmeric 0.2%+probiotic 0.1% and T4=feed basal supplemented with supplemented with turmeric 0.8% + probiotic 0.6%, and T5 = basal diet + Zinc Bacitracin 0.01%. The variables measured were the total bacterial population based on the Total Plate Count (TPC) in the small intestinal digesta of Mojosari ducks. The Data were analyzed using one-way ANOVA. The differences among means were tested using theLeast Significant Difference (LSD) test.